Magnetic Microstructure of Rolled‐Up Single‐Layer Ferromagnetic Nanomembranes. (18th October 2013) - Streubel, Robert; Lee, Jehyun; Makarov, Denys; Im, Mi‐Young; Karnaushenko, Daniil; Han, Luyang; Schäfer, Rudolf; Fischer, Peter; Kim, Sang‐Koog; Schmidt, Oliver G.
<x xml:space="preserve">Abstract</x> The magnetic microstructure of rolled‐up magnetic nanomembranes is revealed both theoretically and experimentally. Two types of nanomembranes are considered, one with a non‐magnetic spacer layer and the other without. Experimentally, by using different materials and tuning the dimensions of the rolled‐up nanomembranes, domain patterns consisting of spiral‐like and azimuthally magnetized domains are observed, which are in qualitative agreement with the theoretical predictions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>